Association of Beta‐Blocker Use With Less Prevalent Joint Pain and Lower Opioid Requirement in People With Osteoarthritis. Issue 7 (7th June 2017) - Valdes, Ana M.; Abhishek, Abhishek; Muir, Kenneth; Zhang, Weiya; Maciewicz, Rose A.; Doherty, Michael
Abstract : Objective: Recent findings suggest that β‐adrenergic blockers have antinociceptive properties. The aim of this study was to compare levels of large‐joint pain between those taking adrenergic blockers and those taking other antihypertensive medications. Methods: Data from the Genetics of Osteoarthritis and Lifestyle (GOAL) study, a secondary‐care cohort of osteoarthritis (OA) patients, were used. Joint pain was assessed using Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain scores in 873 individuals with symptomatic hip and/or knee OA and hypertension, who were taking ≥1 prescription antihypertensive medications. The association between adrenergic blocker prescription and at least moderate joint pain (WOMAC score <75) and use of prescription analgesics was examined using binary logistic regression. Analyses were adjusted for age, sex, body mass index, knee or hip OA, history of joint replacement (at other joints), anxiety, and depression. Results: The use of β‐adrenergic blockers was associated with lower WOMAC pain scores and with a lower prevalence of joint pain after adjustment for demographic variables and comorbidity (adjusted odds ratio [ORadj ] for pain 0.68 [95% confidence interval (95% CI) 0.51, 0.92]; P  < 0.011). No associations with pain were observed with use of alpha‐blockers (ORadj for pain 0.94 [95% CI 0.55, 1.58]) or with any other class of antihypertensive medications. Prescription of beta‐blockers was also associated negatively with opioid use (ORadj for opioids 0.73 [95% CI 0.54, 0.98]; P  < 0.037) and with the use of prescription analgesics in general (ORadj for analgesics 0.74 [95% CI 0.56, 0.94]; P  < 0.032). Conclusion: The use of beta‐blockers is associated with less joint pain and a lower use of opioids and other analgesics in individuals with symptomatic large‐joint OA. This observation needs to be confirmed by other studies.